Respuesta :

Catya
> multiply the second equation by 2 and add it to the first equation.
2(-6x - 7y = -10)
-12x -14y = -20

8x + 14y = 4
-12x - 14y = -20
--------------------
- 4x + 0 = - 16
x = -16/-4
x = 4

> use x = 4 in either equation to find y
8(4) + 14y = 4
32 + 14y = 4
14y = 4 - 32
14y = -28
y = -28/14
y = -2


8x + 14y = 4  | : 2
-6x - 7y = -10

 

 

4x + 7y = 2
-6x - 7y = -10

 

 

4x - 6x = 2 - 10
- 2x = - 8
2x = 8

x = 4


8x + 14y = 4 

14 y = 4 - 8x
14y = 4 - 8*4
14y = 4 - 32

14y = 28

y = 2

ACCESS MORE